2019
DOI: 10.3389/fphar.2019.00514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GLPG/ABBV-2737, a Novel Class of Corrector, Which Exerts Functional Synergy With Other CFTR Modulators

Abstract: The deletion of phenylalanine at position 508 (F508del) in cystic fibrosis transmembrane conductance regulator (CFTR) causes a severe defect in folding and trafficking of the chloride channel resulting in its absence at the plasma membrane of epithelial cells leading to cystic fibrosis. Progress in the understanding of the disease increased over the past decades and led to the awareness that combinations of mechanistically different CFTR modulators are required to obtain meaningful clinical benefit. Today, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…It was also highly functional in primary bronchial epithelial cells from a F508del-homozygous patient (Wang et al, 2018;Singh et al, 2019). ABBV-2737 was demonstrated to rescue functional expression of CFTR in F508del-expressing cells, and such effects were enhanced when it was co-administered with lumacaftor or ABBV-2222(de Wilde et al, 2019. ABBV-3221 also rescued CFTR function in F508del-expressing cells with a greater effect in combination with ABBV-2222 and ABBV-974 (Scanio et al, 2019).…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 92%
See 1 more Smart Citation
“…It was also highly functional in primary bronchial epithelial cells from a F508del-homozygous patient (Wang et al, 2018;Singh et al, 2019). ABBV-2737 was demonstrated to rescue functional expression of CFTR in F508del-expressing cells, and such effects were enhanced when it was co-administered with lumacaftor or ABBV-2222(de Wilde et al, 2019. ABBV-3221 also rescued CFTR function in F508del-expressing cells with a greater effect in combination with ABBV-2222 and ABBV-974 (Scanio et al, 2019).…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 92%
“…Numerous libraries of compounds have been screened by distinct high-throughput screening (HTS) methods and using several cell models. These experimental approaches have been contributing to the identification of small-molecules from different chemical series (Pedemonte et al, 2005a;Van Goor et al, 2009;Van Goor et al, 2011;Phuan et al, 2014;Phuan et al, 2015;Liang et al, 2017;Giuliano et al, 2018;Van der Plas et al, 2018;Veit et al, 2018;Wang et al, 2018;Berg et al, 2019;De Wilde et al, 2019;Merket et al, 2019) (Figure 6). Notably, as cell background may significantly influence the pharmacological rescue of CFTR mutants (Pedemonte et al, 2010), most promising hits should be further validated in well-differentiated cells in order to identify non-cytotoxic and effective compounds that might result in optimal therapeutic benefits in the clinical scenario.…”
Section: Cf-causing Mutations and Progress In Precision Medicinementioning
confidence: 99%
“…In addition, the potential efficacy of novel compounds from academic groups or different pharmaceutical companies have also been revealed in Ussing chamber studies of patient-derived primary nasal epithelial cultures. Interestingly, our group and others observed that patients with the same genotype can exhibit different in-vitro drug responses (11,(25)(26)(27)(28)(29)(30). The molecular basis for interpatient variations in in-vitro response size remains unknown but is thought to be a harbinger of the extent of variability in clinical response size (15).…”
Section: Introductionmentioning
confidence: 85%
“…ABBV-2737 is a second-generation corrector that was well-tolerated in phase I studies and demonstrated to rescue CFTR function in F508del/F508del HBE cells synergistically with VX-809, suggesting that these two molecules act by distinct mechanisms. 73 , 74 In a phase IIa study, ABBV-2737 led to a reduction in sweat Cl – concentration and improved ppFEV 1 , albeit modestly, in individuals with CF homozygous for F508del. 75 ABBV-3221 is another second-generation corrector that demonstrated rescue of F508del-CFTR function with greater effects when in combination with corrector ABBV-2222 and potentiator ABBV-974 (formerly GLPG1837).…”
Section: Cftr Modulator Drugs and Personalized Medicinementioning
confidence: 99%